Relationships between problem behaviors, role changes in areas of work, love, and achievement of adult character qualities among emerging adults - Vosylis, R.; Raižienė, S.; Žukauskienė, R. (Psichologija, 2013)
The goal of the current study is to evaluate the relationships between externalizing and internalizing problems, partner and work commitment, and the achievement of adult character qualities. A sample of 241 Lithuanian emerging adults participated in the study (mean age 22.22, SD = 2.91, 198 women, and 43 men). Participants filled an internet-based questionnaire which consisted of Arnett’s questionnaire on adulthood criteria, additional questions on achieving these criteria, and the Adult Self-report questionnaire which measures internalizing and externalizing problems. Both partner and work commitments were found to be negatively related to anxiety/depression problems, and commitment to work was positively related to intrusive behavior. Achievement of independence was negatively related to anxiety/depression and withdrawal problems. The effect of commitment to work and to partner on anxiety/depression and the effect of commitment to partner on withdrawal was suppressed when it was controlled for achieving independence. Commitment to work positively predicts a more intrusive behavior even when achieving adult character qualities is taken into account.
Keywords: problem behavior; emerging adulthood; role changes; achievement of adulthood criteria